Robust Mobile Cloud Services Through Offline Support - Omwenga Momanyi, Maxwell; Sansa-Otim, Julianne Suzanne; Namulindwa Lumala, Agnes F. (IEEE, 2012)
Cloud computing improves the efficiency of mobile applications. This is because data storage and processing are moved from the low resourced mobile devices to the cloud. Mobile cloud computing however, faces the challenge of intermittent cellular network connection since it is through the connection that services are reached. In this paper we argue that providing mobile cloud applications with temporary off-line file storage increases their robustness without burdening the low resourced mobile handset. We develop a module that offers off-line support which we plug into a mobile cloud calendar and we call it MobiCal.
Keywords: Mobile Cloud Computing; Off-line Support; Robust Application